The newscast in the function of social consciousness during Covid-19: The relationship between journalism, information, empathy fatigue and compassion - Fernandes , Matheus Aparecido Sartori (Seven Editora, 2023)
From the large panels of Times Square to the villages of the Amazon, multimedia information is becoming increasingly ubiquitous in society, and journalism is a fundamental tool for mass communication. The global connection is enabling news to be disseminated in real-time, allowing cities and countries to act in synchrony with each other.With the practical advancement of technology, it's possible to analyze the consequent psychological effects of this evolution. The present work reflects on how the excessive exposure to tragedies can generate a reverse effect to that intended by the press. Empathy fatigue is a phenomenon already observed in the realm of medicine and can be contextualized in the realm of journalism. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-178